The Influence of the Mass Fraction of Catalyst for Oxy-Hydrogen (HHO) Production on the Dry Cell Type of HHO Generator - Tria Puspa Sari; Denny Widhiyanuriyawan; Amajida Sadrina; Ramadan Bimo Anggoro; Rahadi Agung Raharjo; Ryan Rizaldi (Nusantara Science and Technology Proceedings, 2022)
One alternative energy that can e developed in the future is water. The water can produce future fuels, namely hydrogen and oxy-hydrogen, through the electrolysis of water. Electrolysis of water is one way to produce hydrogen into electrical and thermal energy conversion of hydrogen and oxygen. This study used a dry cell type HHO generator to produce Oxy-hydrogen. Oxy-hydrogen consists of two hydrogens and one oxygen or Oxy-hydrogen (HHO). Carried out to determine the optimal performance of the mass fraction of the catalyst on the productivity of Oxy-hydrogen by mixing 2500 ml of air and NaHCO3 as a catalyst. The observed mass catalyst fractions were 0.69, 1.38, 1.77, 2.15, 5 7.5, 10, and 15%. The results showed that the best Oxy-hydrogen production performance using a catalyst was 10% catalyst mass fraction with a production rate of 0.02250 l/s with an efficiency of 36.98%.